Capture and ionization in laser-assisted proton--hydrogen collisions - Niederhausen, Thomas; Thumm, Uwe (My University, 2006)
We calculate electron capture and ionization probabilities for ion–atom collisions in a strong laser field (5×1013W/cm2) by numerically solving the three-dimensional time-dependent Schrödinger equation. For circularly polarized laser fields and an impact energy of 1.2keV∕amu, we find a substantial modification of the electronic dynamics in the H+–H collision system as compared to field-free collisions. In particular, we observe a strong dependence on the initial laser phase and the impact parameter for both capture and ionization, which can be explained using semiclassical arguments.